Antibiotic-Induced, Increased Conjugative Transfer Is Common to Diverse Naturally Occurring ESBL Plasmids in Escherichia coli - Liu, Gang; Bogaj, Karolina; Bortolaia, Valeria; Olsen, John Elmerdahl; Thomsen, Line Elnif (Frontiers in Microbiology, 2019)
Previously, we showed that cefotaxime (CTX) exposure increases conjugative transfer of a blaCTX–M–1 encoding IncI1 plasmid (IncI1/pST49/CTX-M-1) in Escherichia coli in a SOS-independent manner. This study aimed at investigating whether the observation was unique for that plasmid/strain/antibiotic combination or whether antibiotic-induced plasmid transfer (PT) is a more general phenomenon among plasmids in E. coli. Whole genome sequences of 25 E. coli strains were analyzed to identify different extended spectrum beta-lactamases (ESBL) plasmids enabling selection of a diverse collection of plasmids. Experiments were performed following exposure of these strains to 1/2 minimal inhibitory concentration (MIC) of CTX, ampicillin (AMP), or ciprofloxacin (CIP) before conjugation experiments. The frequency of PT was measured and compared to that of donors not exposed to antibiotics. Reverse-transcribed-quantitative real time polymerase chain reaction (RT-qPCR) was used to measure mRNA levels of five PT genes and two SOS response genes in donors exposed to antibiotics. The PT of eight strains (30.8% of strains tested) with IncI1/pST7/CTX-M-1, IncI1/pST49/CTX-M-1, IncI1/pST3/CTX-M-1, IncI1/pST293/CTX-M-1, IncI1/pST295/CTX-M-1, IncI1/pST16/CTX-M-55, and IncFII/CTX-M-14 (n = 2) plasmids was significantly increased following antibiotic exposure. CTX increased PT in all of these eight strain/plasmid combinations, AMP and CIP increased the PT in six and three strains, respectively. RT-qPCR showed that PT genes were up-regulated in the presence of the three antibiotics, whereas SOS-response genes were up-regulated only following CIP exposure. Our findings reveal that antibiotics can increase PT in E. coli strains with various ESBL plasmids. Thus, antibiotic-induced conjugative transfer of ESBL plasmids appears to be a common phenomenon in E. coli, having important implications for assessing the risks of antibiotic use.